Parallel evolution in human populations: A biocultural perspective. Issue 6 (4th September 2022) - Balentine, Christina M.; Bolnick, Deborah A.
Abstract: Parallel evolution—where different populations evolve similar traits in response to similar environments—has been a topic of growing interest to biologists and biological anthropologists for decades. Parallel evolution occurs in human populations thanks to myriad biological and cultural mechanisms that permit humans to survive and thrive in diverse environments worldwide. Because humans shape and are shaped by their environments, biocultural approaches that emphasize the interconnections between biology and culture are key to understanding parallel evolution in human populations as well as the nuances of human biological variation and adaptation. In this review, we discuss how biocultural theory has been and can be applied to studies of parallel evolution and adaptation more broadly. We illustrate this through four examples of parallel evolution in humans: malaria resistance, lactase persistence, cold tolerance, and high‐altitude adaptation.